Convenient synthesis of allenylphosphoryl compounds via Cu-catalysed couplings of P(O)H compounds with propargyl acetates. Issue 38 (21st April 2016) - Shen, Ruwei; Luo, Bing; Yang, Jianlin; Zhang, Lixiong; Han, Li-Biao
Abstract : A novel Cu-catalysed substitution reaction of propargyl acetates with P(O)H compounds is developed to afford allenylphosphoryl compounds in high yields. A plausible mechanism involving the nucleophilic interception of Cu-allenylidene intermediates is proposed. Abstract : A novel Cu-catalysed substitution reaction of propargyl acetates with P(O)H compounds is developed to afford allenylphosphoryl compounds via C–P bond coupling in high yields under mild conditions. A plausible mechanism involving the nucleophilic interception of the Cu-allenylidene intermediates is proposed.